Who's who in finance, 1975-76 - Found, Peter (Epping : Gower Press, 1975)
Who's Who in Finance was first published in 1972 with the intention, "to open politely and with the co-operation of the (financial) community the avenues of introduction and communication exchange'. The aim of this new edition, which has been completely up-dated and revised, is to continue the fulfillment of this valuable role. This directory of the holders of the most influential posts in the financial sector, both in the City and elsewhere, is therefore a reflection of the willing co-operation received from the members of the British financial community.
Includes index.
rpm 11/04/2018
Loans
Keywords: Finance; Britain